The detection of SARS-CoV-2 using reverse transcription loop-mediated isothermal amplification (RT-LAMP) in developing country - Wibowo, Muhammad Rizky; Harfiani, Erna; Sarmoko, Sarmoko; Nugraha, Yudhi (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2021)
The severe acute respiratory syndrome coronavirus (SARS-CoV-2) has infected the human system resulting in Covid-19, and has spread rapidly worldwide. Therefore, a fast, simple, cost-effective, and accurate detecting tool is required. The standard diagnostic tool of the World Health Organization is the reverse transcription-polymerase chain reaction (RT-PCR). This method detects the presence of viral genetic material in the human body with accurate results. However, it has several limitations in terms of equipment, personnel, duration, and cost. Therefore, a fast, simple, and sensitive alternative detection, is required, one of which is the reverse transcription loop-mediated isothermal amplification (RT-LAMP) that functions under isothermal conditions. This method is battery-driven, hence, easy to move closer to the patient. Conclusively, the RT-LAMP test for SARS CoV-2 diagnosis produces comparable sensitivity to a standard RT-PCR and is more suitable for resource-poor settings, such as rural areas of developing countries.